Management of Book Reading Curriculum in the Family to Develop an Interest in Reading in Early Children - Retoliah, Retoliah; Kasmiati, Kasmiati; Kurniawan, Heru (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Reading books by parents to children in the family is essential to manage properly. This study aimed to find and explain the management of parents' book reading curriculum in early childhood in family life. This study uses qualitative field research, which focuses on examining texts in references and research articles that discuss the introduction of literacy and reading activities in the family. The data collection technique used is documentation in the form of data sources from various reference sources, both journal articles, research results, and reference books. Data analysis techniques are carried out by reviewing data based on the scientific point of view, analyzing and criticizing the data studied comprehensively, and presenting the results in its findings. The results of his research are that the management of the curriculum for reading books for parents to children is carried out through (1) management in building family literacy goals which are carried out by getting used to reading books; (2) managing the provision of reading materials in the family which is carried out by organizing and managing a place for books in a strategic family room and managing reading interesting books, according to interests, and by the stages of child development; (3) management of routine reading activities so that it becomes a habit in the family; (4) award-based assessment management of book reading activities that have been carried out.